Low-temperature carbonate melt reaction preparation method of metal-based solid oxide electrolyte membrane

Through the carbonate melt reaction method, Na2CO3-K2CO3 eutectic salt dissolves the precursor reactants and performs a low-temperature melt reaction, which solves the problems of low density and insufficient conductivity of the traditional MS-SOFC electrolyte film, and achieves efficient and low-cost electrolyte film densification.

CN119725648AActive Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311252642.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

Traditional metal-supported solid oxide fuel cell (MS-SOFC) sintered electrolyte membranes at high temperatures have problems such as low density and insufficient conductivity, resulting in increased production cost and difficulty.

Method used

The carbonate melt reaction method was adopted to dissolve the high-melting point precursor reactants through the eutectic salt of Na2CO3-K2CO3, and carry out low-temperature melt reaction to form a micron-scale dense electrolyte film.

Benefits of technology

Low-temperature densification of the electrolyte film is achieved, sintering temperature is reduced, volatilization and segregation of substances and elements is avoided, conductivity and density is improved, and preparation cost and difficulty is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004470771890000011
    Figure HDA0004470771890000011
  • Figure HDA0004470771890000012
    Figure HDA0004470771890000012
  • Figure HDA0004470771890000021
    Figure HDA0004470771890000021
Patent Text Reader

Abstract

The invention provides a low-temperature carbonate melt reaction method for preparing a metal-based electrolyte film, and provides a strategy for solving the key problem that sintering temperatures of all parts of a metal-based solid oxide battery are different. According to the preparation method, Na2CO3-K2CO3 eutectic molten salt is introduced, so that a precursor reactant with a high melting point is dissolved in the eutectic melt and reacts, a target product crystal is separated out after supersaturation and gradually grows and is continuously generated, and finally, a micron-sized compact electrolyte film can be obtained. According to the method, a solid-solid system in a traditional sintering method is converted into a solid-liquid system through simple low-temperature co-melt reaction, and the mass transfer rate and the reaction rate are higher; compared with a common physical film preparation method of a metal-based solid oxide battery, the carbonate low-temperature melt method is simple in process, does not need expensive equipment, can greatly reduce the preparation cost and difficulty of the metal-based solid oxide battery, and has industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal-based solid oxide electrolytes, and in particular relates to a method for densifying a metal-based electrolyte film at low temperature by utilizing carbonate melt reaction. Background Art

[0002] Solid oxide fuel cell (SOFC) is an electrochemical energy conversion device that can directly convert fuel chemical energy into electrical energy. It is greener and more efficient than traditional fuel combustion power generation. However, traditional SOFC faces problems such as sealing difficulties, high material costs and poor resistance to thermal shock when operating at high temperatures, which restricts the further development of SOFC. Metal-supported solid oxide fuel cell (MS-SOFC) is the third generation of SOFC. It uses low-cost stainless steel and other metal materials as cell supports and connectors, which is conducive to solving the problems of poor strength, difficult packaging, and long startup time brought by the traditional SOFC all-ceramic design.

[0003] The commonly used metal substrates for MS-SOFC are nickel-based and iron-based metals. Among them, Changsing Hwang et al. prepared La on a porous nickel metal substrate using atmospheric plasma spraying technology. 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ Electrolyte, followed by annealing at 1000°C. Compared with nickel-based metals, iron-based metals are cheaper and have a thermal expansion coefficient that is more compatible with ceramic electrolyte membranes. et al. prepared ScYSZ electrolyte on a stainless steel substrate using a co-sintering method and prepared Ce using a magnetron sputtering method. 0.9 G 0.1 O 2-δ Isolation layer. Yan Dong et al. used Ni-Fe alloy as the metal substrate and prepared the electrolyte membrane by high-temperature co-sintering. The addition of Fe element can enhance the oxidation resistance of the nickel-based metal substrate. In general, the sintering temperatures of various materials of MS-SOFC are different. In order to prevent the metal substrate from sintering and oxidation at high temperatures, physical methods such as pulsed laser and physical vapor deposition are usually used to prepare the electrolyte membrane. Specific equipment is required and it is difficult to expand production, resulting in low electrolyte density and insufficient conductivity, which greatly increases the preparation cost and difficulty of metal-supported solid oxide batteries. Therefore, the important direction of MS-SOFC research at this stage is still to explore low-temperature and low-cost electrolyte membrane preparation processes. Summary of the invention

[0004] In order to solve the problems of the prior art, the present invention provides a low-temperature densification method for a metal-based solid oxide electrolyte membrane based on a carbonate melt reaction. The present invention utilizes the significant advantages of melt growth, such as high crystal purity and good integrity, and introduces a Na2CO3-K2CO3 eutectic salt, so that a high-melting-point precursor reactant is dissolved in the eutectic and reacts, and after reaching supersaturation, the target product crystal is precipitated and gradually grows and grows together, and finally a micron-level dense electrolyte film can be obtained. The present invention provides a strategy for solving the key problem of different sintering temperatures of various parts of a metal-based solid oxide battery.

[0005] The present invention provides a low-temperature densification method for a metal-based solid oxide electrolyte membrane based on a carbonate melt reaction, comprising the following steps:

[0006] (1) Metal powder and pore-forming agent powder are mixed, pressed into tablets, and calcined in an argon atmosphere to obtain a metal substrate.

[0007] (2) Preparing a precursor oxide powder into a precursor oxide slurry, then uniformly coating the precursor oxide slurry on a metal substrate, and calcining the precursor oxide slurry at a low temperature in air to remove organic matter, thereby obtaining a precursor oxide coating.

[0008] (3) Evenly mixing a certain amount of carbonate eutectic powder with precursor carbonate powder and precursor oxide powder, transferring the mixture to an alumina crucible, and covering and embedding the mixture on the coating prepared in step (2).

[0009] (4) placing the crucible from step (3) into a tubular furnace to carry out melt reaction in an argon atmosphere, and after the reaction is completed, acid washing and drying are performed to obtain a dense metal-based solid oxide electrolyte membrane.

[0010] The metal powder is one of nickel powder and nano 430 stainless steel powder; the pore former powder is BaCO3 powder;

[0011] The precursor oxide powder is (ZrO2) 0.92 (Y2O3) 0.08 (8YSZ), which is a raw material for preparing electrolyte films;

[0012] The precursor carbonate powder is BaCO3, which is the raw material for preparing electrolyte film;

[0013] The carbonate eutectic powder is composed of a mixture of Na2CO3 and K2CO3; after melting, the eutectic powder dissolves the precursor carbonate powder and the precursor oxide powder, causing them to react with each other, thereby providing a melting environment for crystal growth;

[0014] The melting points of the precursor carbonate and the precursor oxide are both higher than that of the carbonate eutectic powder.

[0015] Furthermore, in the above technical solution, in step (1), the particle size of the nickel powder is 500nm-1μm, and the particle size of the nano 430 stainless steel powder is 100-500nm; (ZrO2) 0.92 (Y2O3) 0.08 The particle size of (8YSZ) is 10nm~200nm.

[0016] Furthermore, in the above technical solution, in step (1), the pore-forming agent accounts for 20 to 40% of the total mass of the metal powder.

[0017] Furthermore, in the above technical solution, in step (1), the thickness of the pressed sheet is 1 to 1.2 mm.

[0018] Furthermore, in the above technical solution, in step (1), the calcination temperature of the metal substrate is 750-800° C., and the heat preservation time is 5-10 hours.

[0019] Furthermore, in the above technical scheme, in step (2), surfactants (triethanolamine), dispersants (butyl benzyl phthalate), binders (polyvinyl butyral resin), solvents (ethanol, butanone) and other organic substances are also added to the precursor oxide slurry, and the precursor oxide powder is mixed with the surfactants, dispersants, binders, solvents and other organic substances to obtain the precursor oxide slurry; the percentage content of each component in the precursor oxide slurry is: precursor oxide powder 20-33wt%, ethanol 41-51wt%, butanone 19-20wt%, triethanolamine 1-1.2wt%, polyvinyl butyral resin 3-4wt%, butyl benzyl phthalate 2-3wt%.

[0020] Furthermore, in the above technical solution, in step (2), the coating method is normal pressure or negative pressure impregnation.

[0021] Furthermore, in the above technical solution, in step (2), the calcination temperature is 400-600° C. and the calcination time is 2-5 hours.

[0022] Furthermore, in the above technical solution, in step (3), the molar ratio of Na2CO3 to K2CO3 in the carbonate eutectic powder is 1.2 to 1.6:1, the eutectic point is 710°C, and the total amount of the substance is 0.02 to 0.04 mol.

[0023] Furthermore, in the above technical solution, in step (3), the precursor carbonate BaCO3 powder accounts for 20 to 40 mol% of the carbonate eutectic powder.

[0024] Furthermore, in the above technical scheme, in step (3), the added precursor carbonate BaCO3 is in excess of the precursor oxide 8YSZ powder, and the molar ratio of the metal elements in the precursor carbonate powder and the precursor oxide powder is 3:1 to 9:1, that is, Ba:(Zr+Y)=3:1 to 9:1 mol / mol.

[0025] Furthermore, in the above technical solution, in step (4), the melt reaction temperature is 750 to 800° C., and the reaction time is 12 to 48 hours.

[0026] Furthermore, in the above technical solution, in step (4), the acid washing is performed by soaking and washing in a 0.5M acetic acid solution overnight.

[0027] Furthermore, in the above technical solution, the thickness of the obtained dense ceramic film is 5 to 10 μm.

[0028] The present invention is beneficial in that:

[0029] (1) The electrolyte film is prepared by a simple low-temperature melt reaction, where the refractory reactant powder is dissolved in a suitable molten salt for reaction, thereby converting the solid-solid system in the traditional sintering method into a more uniform solid-liquid system, greatly improving mass transfer and reaction rate and improving interface contact;

[0030] (2) A low-temperature electrolyte film densification technology has been developed. The densification temperature can be reduced to below 1000°C, which avoids the volatilization and segregation of substances and elements, is conducive to maintaining the stoichiometric ratio of the electrolyte membrane and preparing high-performance solid oxide electrolyte membranes;

[0031] (3) This method does not require sintering the electrolyte membrane under vacuum or inert atmosphere protection, which prevents the metal substrate from high-temperature oxidation and sintering failure while obtaining a dense electrolyte film, solving the key problem of different sintering temperatures of different parts of the metal-based SOFC.

[0032] (4) Compared with the physical film preparation method commonly used in metal-based SOFC, the carbonate low-temperature melt method is simple in preparation process and does not require expensive equipment. It can greatly reduce the cost and difficulty of metal-based SOFC preparation and has the potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the principle of preparing metal-based dense electrolyte membrane by the low-temperature carbonate melt reaction method described in the present invention.

[0034] Figure 2The metal nickel substrate with added pore former prepared in step 1 of Example 1 of the present invention, wherein a) is the metal nickel substrate obtained after calcining with the pore former; b) is the metal substrate after calcination and then pickling to remove the pore former (the pore former of the metal substrate is removed by pickling to show the pore size morphology of the porous metal substrate. In the membrane forming process of the embodiment, the pore former is retained in the metal substrate for melt reaction until it is removed together with excess carbonate melt in pickling in step 3).

[0035] Figure 3 This is an electron microscope image of the precursor oxide coating prepared in step 2 of Example 1 of the present invention, wherein a) is the coating surface; b) is the coating cross-section.

[0036] Figure 4 This is an electron microscope image of the metal-based electrolyte membrane prepared in step 3 of Example 1 of the present invention, wherein a) is the surface of the electrolyte membrane; b) is the cross-section of the electrolyte membrane. DETAILED DESCRIPTION

[0037] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0038] Example 1

[0039] Step 1: Preparation of nickel metal substrate. Weigh 1g of nickel powder (particle size 500nm~1μm) and 0.2g of BaCO3 and grind them evenly in a mortar. Use a φ20mm mold to press the tablets with a thickness of about 1mm. Then put it into a tube furnace and slowly heat it to 800℃ under 100ml / min argon atmosphere, and keep it warm for 5h. In the low temperature section, slowly heat it to 500℃ at a rate of 0.5℃ / min, and then heat it to 800℃ at 1℃ / min.

[0040] Step 2: Prepare the precursor oxide coating. Use 10g of nano 8YSZ (particle size of about 10nm) and 10g of micro-nano 8YSZ (particle size of about 200nm) powder as starting materials, 50.4g of anhydrous ethanol and 20g of butanone as solvents, and 1.2g of triethanolamine as a surfactant, and mix and ball-mill for 24 hours. Then, continue to add 3.6g of butyl benzyl phthalate and 2.7g of polyvinyl butyral as dispersants and binders and ball-mill for 24 hours to obtain a uniformly dispersed 8YSZ slurry. 8YSZ is coated on the metal substrate by three repeated atmospheric pressure impregnations, with a single immersion time of 1min, and then slowly heated to 400℃ in a muffle furnace at 0.5℃ / min and calcined for 3h to remove organic matter. The morphology of the obtained precursor oxide coating is as follows: Figure 3 shown.

[0041] Step 3: Prepare BaZr 0.85 Y 0.15 O 3-δ(BZY) solid oxide electrolyte membrane. Weigh 0.04 mol of Na2CO3 and K2CO3 powder (wherein the molar ratio of Na2CO3 to K2CO3 is 1.5), 0.008 mol of BaCO3 powder and 0.0008 mol of nano 8YSZ powder (particle size is about 10 nm); that is, BaCO3 accounts for 20 mol% of the total mass of Na2CO3-K2CO3, and Ba:(Zr+Y)=9:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover with the precursor oxide coating of embedding step 2, and react at 800°C for 12 hours under 100 ml / min argon atmosphere. Finally, soak in 0.5 M acetic acid solution overnight to clean the excess carbonate melt and the BaCO3 pore-forming agent in the metal substrate. After drying, a metal-based BZY electrolyte membrane with a thickness of about 10 μm and a morphology as shown in the figure. Figure 4 shown.

[0042] Example 2

[0043] Step 1: Preparation of nickel metal substrate. Same as step 1 in Example 1.

[0044] Step 2: Prepare a precursor oxide coating, which is the same as step 2 in Example 1.

[0045] Step 3: Prepare BZY solid oxide electrolyte membrane. Weigh 0.02 mol of Na2CO3 and K2CO3 powder (wherein the ratio of Na2CO3 to K2CO3 is 1.2), 0.006 mol of BaCO3 powder and 0.0009 mol of nano 8YSZ powder (particle size is about 10 nm); that is, BaCO3 accounts for 30 mol% of the total amount of Na2CO3-K2CO3 eutectic salt, Ba: (Zr + Y) = 6: 1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the 8YSZ coating in step 2, and react at 800 ° C for 12 hours under 100 ml / min argon atmosphere. After the reaction is completed, use 0.5M acetic acid solution to soak and clean overnight, and then dry to obtain a dense metal-based BZY electrolyte membrane.

[0046] Example 3

[0047] Step 1: Preparation of nickel metal substrate. Weigh 1g of nickel powder (particle size 500nm-1μm) and 0.3g of BaCO3 and grind them evenly in a mortar. Use a φ20mm mold to press the tablets with a thickness of about 1.1mm. Then put them into a tube furnace and slowly heat them to 750℃ under 100ml / min argon atmosphere for 10h. In the low temperature section, slowly heat them to 500℃ at a rate of 0.5℃ / min, and then heat them to 750℃ at 1℃ / min.

[0048] Step 2: Prepare a precursor oxide coating, which is the same as step 2 in Example 1.

[0049] Step 3: Prepare BZY solid oxide electrolyte membrane. Weigh 0.04 mol of Na2CO3 and K2CO3 powder (wherein the ratio of the amount of Na2CO3 to K2CO3 is 1.6), 0.016 mol of BaCO3 powder and 0.005 mol of nano 8YSZ powder (particle size is about 10 nm); that is, BaCO3 accounts for 40 mol% of the total mass of Na2CO3-K2CO3, and Ba:(Zr+Y)=3:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the precursor oxide coating of step 2, and react at 800°C for 24 hours under 100 ml / min argon atmosphere. Finally, use 0.5M acetic acid solution to clean overnight, and after drying, you can get a metal-based BZY electrolyte membrane.

[0050] Example 4

[0051] Step 1: Preparation of nickel metal substrate. Same as step 1 in Example 1.

[0052] Step 2: Prepare the precursor oxide coating. Take 20g of nano 8YSZ (particle size of about 10nm) and 20g of micro-nano 8YSZ (particle size of about 200nm) powder as the starting material, 50.4g of anhydrous ethanol and 20g of butanone as solvents, 1.2g of triethanolamine as a surfactant, and mix and mill for 24h, then continue to add 3.6g of butyl benzyl phthalate and 2.7g of polyvinyl butyral as dispersants and binders and mill for 24h to obtain a uniformly dispersed 8YSZ slurry. Use a suction bottle to apply a pressure of -0.05MPa, and apply the 8YSZ slurry to the nickel metal substrate by negative pressure impregnation. The impregnation time is 1min, and then slowly increase the temperature to 400℃ in a muffle furnace at 0.5℃ / min and calcine for 3h to remove organic matter.

[0053] Step 3: Prepare BZY solid oxide electrolyte membrane. Weigh 0.03 mol of Na2CO3 and K2CO3 powder (wherein the ratio of Na2CO3 to K2CO3 is 1.5), 0.006 mol of BaCO3 powder and 0.0009 mol of nano 8YSZ powder (particle size is about 10 nm); that is, BaCO3 accounts for 20 mol% of the total mass of Na2CO3-K2CO3, and Ba:(Zr+Y)=6:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the precursor oxide coating of step 2, and react at 750°C for 48 hours under 100 ml / min argon atmosphere. Finally, use 0.5 M acetic acid solution overnight to clean the excess carbonate melt and the BaCO3 pore-forming agent in the metal substrate, and then dry to obtain a metal-based BZY electrolyte membrane.

[0054] Example 5

[0055] Step 1: Preparation of 430 stainless steel substrate. Weigh 1 g of 430 stainless steel powder (particle size of about 100 nm) and 0.4 g of pore-forming agent BaCO3 in a mortar and grind them evenly. Use a φ20 mm mold to press the tablets to a thickness of about 1.2 mm. Then put them in a tube furnace and slowly heat them to 750°C in an argon atmosphere of 100 ml / min for 10 hours. In the low temperature section, slowly heat them to 500°C at 0.5°C / min, and then heat them to 750°C at 1°C / min.

[0056] Step 2: Prepare a precursor oxide coating, which is the same as step 2 in Example 1.

[0057] Step 3: Prepare BZY solid oxide electrolyte membrane. Same as step 3 in Example 1.

[0058] Many embodiments can be listed above. For example, the grain size of the electrolyte membrane can be changed by adjusting the reaction temperature or time. In addition, the density of the electrolyte membrane can be further improved by repeated growth. The ratio of the carbonate eutectic to the precursor carbonate and the ratio of the precursor carbonate to the precursor oxide are both adjustable. In theory, as long as the precursor carbonate and the precursor oxide can be dissolved in the molten eutectic salt to react, and the target product can reach supersaturation in the melt and precipitate, a dense film can be prepared according to the carbonate melt reaction method proposed in the present invention.

Claims

1. A method for low-temperature densification of a metal-based solid oxide electrolyte membrane based on a carbonate melt reaction, characterized in that: The method comprises the following steps: (1) mixing metal powder with a pore-forming agent, pressing into tablets, and calcining to obtain a metal substrate; (2) preparing a precursor oxide powder into a slurry, uniformly coating the slurry on a metal substrate, and calcining the slurry to remove organic matter, thereby obtaining a precursor oxide coating; (3) mixing the carbonate eutectic powder, the precursor carbonate powder and the precursor oxide powder uniformly, transferring the mixture to an alumina crucible, and covering and encapsulating the coating prepared in step (2); (4) placing the crucible of step (3) into a tubular furnace for melt reaction, followed by pickling and drying to obtain a metal-based electrolyte film; The metal powder is one of nickel powder and nano 430 stainless steel powder, the pore former is BaCO3 powder, and the precursor oxide powder is (ZrO2) 0.92 (Y2O3) 0.08 , the precursor carbonate powder is BaCO3, and the carbonate eutectic powder is composed of Na2CO3 and K2CO3.

2. The method according to claim 1, characterized in that In step (1), the calcination temperature is 750-800° C. and the calcination time is 5-10 hours.

3. The method according to claim 1, characterized in that In step (1), the pore-forming agent accounts for 20 to 40% of the mass of the metal powder.

4. The method according to claim 1, characterized in that: In step (3), the molar ratio of Na2CO3 to K2CO3 in the carbonate eutectic powder is 1.2 to 1.6, the eutectic point is 710°C, and the total amount of the substance is 0.02 to 0.04 mol.

5. The method according to claim 1, characterized in that In step (3), the precursor carbonate powder accounts for 20 to 40 mol% of the carbonate eutectic powder.

6. The method according to claim 1, characterized in that In step (3), the molar ratio of the metal elements in the precursor carbonate powder to the precursor oxide powder is 3:1 to 9:

1.

7. The method according to claim 1, characterized in that In step (2), triethanolamine, butyl benzyl phthalate, polyvinyl butyral resin, ethanol, and butanone are further added to the slurry, and the percentage of each component in the slurry is: 20-33wt% of precursor oxide powder, 41-51wt% of ethanol, 19-20wt% of butanone, 1-1.2wt% of triethanolamine, 3-4wt% of polyvinyl butyral resin, and 2-3wt% of butyl benzyl phthalate.

8. The method according to claim 1, characterized in that In step (4), the temperature of the melt reaction is 750-800° C.; and the reaction time is 12-48 hours.

9. The method according to claim 1, characterized in that: In step (2), the coating method is atmospheric pressure or negative pressure impregnation; the calcination temperature is 400-600° C., and the calcination time is 2-5 hours.

10. The method according to claim 1, characterized in that The thickness of the obtained metal-based electrolyte film is 5 to 10 μm.

Citation Information

Patent Citations

  • Composite oxide, sintering body, solid electrolyte and manufacturing method thereof

    CN101901922A

  • Composite fuel battery solid electrolyte made of low-temperature phase change material and preparation method

    CN108539234A

  • Electrolyte material for solid oxide fuel cell and method for producing precursor thereof

    CN112585791A

  • Process method for preparing ceramic membrane and ceramic membrane fuel cell

    CN115332592A

  • Method for mfg. anode carried thin film medium-temp. solid oxide fuel cell

    CN1402372A